FIKIH EKOLOGI DAN KEARIFAN TRADISIONAL: TINJAUAN TERHADAP KONSEP IHYÂ AL-MAWÂT DAN HIIMÂ - Rusli Rusli (State Institute of Islamic Studies (IAIN) Palu, 2008)
This paper deals with the concepts related to the protection and preservation of ecology. It is argued that the Islamic concern to this issue is significantly great. It is proven by the existence of ihyâ al-mawât (revival of dead land) and himâ (conservation area), which give serious concern to the protection of land. Both concepts indicate that such malicious acts to lands are seriously prohibited. Otherwise, acts to cultivate lands are necessarily encouraged. Besides, customary laws (‘urf) which are universally friendly to ecology could be used as means of protecting ecology and environment.Kata Kunci: fikh ekologi, kearifan lokal, hifz al-bî’ah, ihyâ al-mawât, himâ, ‘urf